Involvement of Insulin Signaling Disturbances in Bisphenol A-Induced Alzheimer’s Disease-like Neurotoxicity - Tingwei Wang (Nature Portfolio, 2017)
Abstract Bisphenol A (BPA), a member of the environmental endocrine disruptors (EDCs), has recently received increased attention because of its effects on brain insulin resistance. Available data have indicated that brain insulin resistance may contribute to neurodegenerative diseases. However, the associated mechanisms that underlie BPA-induced brain-related outcomes remain largely unknown. In the present study, we identified significant insulin signaling disturbances in the SH-SY5Y cell line that were mediated by BPA, including the inhibition of physiological p-IR Tyr1355 tyrosine, p-IRS1 tyrosine 896, p-AKT serine 473 and p-GSK3α/β serine 21/9 phosphorylation, as well as the enhancement of IRS1 Ser307 phosphorylation; these effects were clearly attenuated by insulin and rosiglitazone. Intriguingly, Alzheimer’s disease (AD)-associated pathological proteins, such as BACE-1, APP, β-CTF, α-CTF, Aβ 1–42 and phosphorylated tau proteins (S199, S396, T205, S214 and S404), were substantially increased after BPA exposure, and these effects were abrogated by insulin and rosiglitazone treatment; these findings underscore the specific roles of insulin signaling in BPA-mediated AD-like neurotoxicity. Thus, an understanding of the regulation of insulin signaling may provide novel insights into potential therapeutic targets for BPA-mediated AD-like neurotoxicity.